Pengaruh Variasi Herbal terhadap Organ dalam Broiler - Sulistyoningsih, Mei (Prosiding KPSDA, 2015)
This research assessing the influence of various herbs on internal organs broiler . This study using random complete the design, with four replication. Treatment of this research is P0 (Control , commercial feed without additional herbs), P1 (Commercial feed + Herbs of the tongue crocodiles), P1 (Commercial feed + noni), and P3 (Commercial feed + ginger). The subject of research is doc who are being guarded broiler after hatching, until age five weeks, then taken data research. Parameters taken on this research is body weight , the weight of the liver, the heart, gizzard, the intestines, and spleen. This research result indicates , there is a significant difference variations due to the provision of herbs on body weight and weights broiler liver ( p < 0.05), but there is no difference on empedal, the heart, the intestines, and spleen ( p >0.05 ).